Evaluation of Çanakkale - Kilitbahir Castle Museum and environmental landscape - Yavuz Alkan (Turkish Journal of Forestry, 2024)
Museums have played an important role in the spread of national and international culture in the historical process, in transferring it from generation to generation and in increasing intercultural interaction and awareness. In this study, where the Kilitbahir Castle Museum is examined in this respect, the inside of the castle and its immediate surroundings are examined within the scope of landscape values. The village of Kilitbahir, which contains the museum within its borders, is located opposite the province of Çanakkale. The distance between this village, which is separated by the Dardanelles Strait, and the Çanakkale province, to which it is politically connected, is about 3 km. The examination of the museum within the scope of landscape criteria was carried out in two steps. First, structural and vegetative analysis is included depending on the observations made in the field. In the second step, the opinions and thoughts of the user factor depending on the recreational approaches on the research area are revealed. For this purpose, mutual interviews were provided with 100 visitors by chance. The results obtained by the questionnaire were evaluated by using SPSS 15.0 statistical analysis program. The basis of the said evaluation was user satisfaction/dependent variable and the structural and vegetal landscape elements/independent variables affecting it. According to the analysis, the significance level of the relationship between the variables was found to be 0.000 and the R square value was 0.825. In the light of these and similar results, in this study, which is designed to contribute to the optimal use of the research area, suggestions have been developed with common or similar approaches derived from both strategies followed depending on the method.